2012
DOI: 10.1163/092050611x605230
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of a Star-Shaped Poly( ϵ -Caprolactone)–Ibuprofen Conjugate

Abstract: A series of novel star-shaped poly(ϵ-caprolactone) (PCL) biodegradable polyesters were synthesized through ring-opening polymerization of ϵ-caprolactone in the presence of a poly(amidoamine) (PAMAM) dendrimer initiator. The polymers (PAMAM/PCLs) were obtained with a high yield (92%) and a number-average molecular weight of up to 14 000 g/mol. The nonlinear structure of PAMAM/PCLs was confirmed by nuclear magnetic resonance, gel-permeation chromatography, thermogravimetric analysis and differential scanning cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…It was noted that there are unreacted hydroxyl groups in the bis-MPA molecule. This fact may be attributed to the change in the density and distribution of hydroxyl groups on the surface of the initiator and the stearic hindrance of the attached growing copolymer chains [ 20 ]. However, it was difficult to find and discriminate unreacted hydroxyl groups of bis-MPA moiety on 1 H-NMR spectra.…”
Section: Resultsmentioning
confidence: 99%
“…It was noted that there are unreacted hydroxyl groups in the bis-MPA molecule. This fact may be attributed to the change in the density and distribution of hydroxyl groups on the surface of the initiator and the stearic hindrance of the attached growing copolymer chains [ 20 ]. However, it was difficult to find and discriminate unreacted hydroxyl groups of bis-MPA moiety on 1 H-NMR spectra.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of monomer present in the reaction mixture was confirmed by NMR and IR spectroscopies. Chloroform was chosen because it is the preferred solvent to terminate the lipase reactions; despite the use of this solvent in this one step, our overall synthetic methods are greener than traditional methods; other methods to achieve similar reactions utilize excess carbodiimides, chlorinated solvents, and metal catalysts often used in contrast to solvent‐free, catalytic reactions, safer solvents, and enzyme catalyst. GPC analysis indicated that M w values were moderate and PDI values narrow (Table ) substantiating that an additional purification step was unnecessary.…”
Section: Resultsmentioning
confidence: 99%
“…It was noted that there are unreacted hydroxyl groups of aescin in the resulting branched copolymers. This fact may be attributed to the change in the density and distribution of hydroxyl groups on the surface of the initiator and the stearic hindrance of the attached copolymer chains [20]. The resulting branched copolymers were characterized by 1 H, 13 C NMR and FTIR analysis (Figure 1, as well as Figures S1 and S2, Supplementary Material).…”
Section: Structural Characterization Of the Copolymeric Matricesmentioning
confidence: 99%